Data Sharing and the Idea of Ownership. Issue 1 (2nd January 2017) - Montgomery, Jonathan
Abstract : Ideas about ownership are sometimes used in discussions of data sharing in personalised medicine. Personal health data are thought by many to be 'theirs'. Paradoxically, personalised medicine (at least in the context of genomics) relies on the aggregation of private data into a dataset that is held as a form of knowledge commons. When the notions of private and common property that lie behind this discourse are made explicit we can use thinking about the justifications and jurisprudence of property both to clarify the persuasiveness and limits of such claims, and also how they differ from other principles that are at stake in the interplay between individual and collective goods in the delivery of personalised medicine. This shows that ownership might more plausibly lie with health professionals than patients. In a socialised medicine system, such as the NHS, such professionals are agents of the state and ownership would lie with the commons rather than any individual. Common rather than private ownership of genomic information may be more appropriate.